MARKETING COMMUNICATIONS IN MANAGING THE MARKETING ACTIVITY OF BUILDING MATERIALS MANUFACTURING ENTERPRISES (Marketing Journal, 2026)
This article examines the effective management of marketing communications in enterprises producing construction materials. Within the scope of the study, the concept of Integrated Marketing Communications (IMC) is analyzed, and the optimal selection of co mmunication tools in the B2B sector as well as their synergistic effects are explored. Methodologically, the research employs content analysis, comparative analysis, and interpretation of statistical data. As a result, practical recommendations for optimiz ing marketing communications in the context of the construction industry are developed. № 1 -SON YANVA R, 202 6-YIL 381
Keywords: marketing communications; construction materials; integrated marketing communications (IMC); B2B marketing; digital transformation; brand management